Revisiting the Performance of DNS Queries on a DNS Hierarchy Testbed over Dual-Stack. (12th March 2021) - Adiwal, Sanjay; Rajendran, Balaji; Shetty D, Pushparaj; Palaniappan, Gopinath
Abstract: The exponential growth of IoT devices and their need to use IPv6 addresses has the potential to create load stress on the existing DNS infrastructure and it is imperative that DNS servers to be deployed on IPv6 networks. The DNS query latency from a particular Internet vantage point for IPv4 and IPv6 network cannot be compared directly due to variations in the number of hops of query on IPv4 and IPv6 communication networks. Moreover, there is no assurance that DNS server in the hierarchy is hosted on a dual-stack. This work brings out the DNS query resolution latency over the IPv4 and IPv6 protocol stacks with better accuracy. The experiments are carried out by setting up a complete DNS hierarchy (ROOT, TLD, STLD, TTLD and recursive resolver) on dual IP stack (IPv4 and IPv6), enabling both forward and reverse lookup tree on a live testbed, ensuring a constant number of hops between the recursive resolver and each of the DNS servers in the hierarchy. This live testbed is a first of its kind and is made available for Internet researchers. The operational issues encountered during this deployment and service provisioning are discussed and documented in this paper. This paper also gives a clear illustration and provides reference guidelines for the DNS hierarchy setup, and also aims to bridge the knowledge gap required for deploying DNS over IPv6.